Isolation of a 2-picolinic acid-assimilating bacterium and its proposed degradation pathway. (December 2017) - Zheng, Chunli; Wang, Qiaorui; Ning, Yanli; Fan, Yurui; Feng, Shanshan; He, Chi; Zhang, Tian C.; Shen, Zhenxing
Graphical abstract: Highlights: A Burkholderia sp. which can aerobically utilize 2-picolinic acid was isolated. Growth and degradation kinetic models were established. The degradation pathway of 2-picolinic acid was reported. The ring cleavage product of 2-picolinic acid was captured and analyzed. FT-ICR-MS and ATR-FTIR were used to deduce the biodegradation pathway. Abstract: Burkholderia sp. ZD1, aerobically utilizes 2-picolinic acid as a source of carbon, nitrogen and energy, was isolated. ZD1 completely degraded 2-picolinic acid when the initial concentrations ranged from 25 to 300 mg/L. Specific growth rate ( μ ) and specific consumption rate ( q ) increased continually in the concentration range of 25–100 mg/L, and then declined. Based on the Haldane model and Andrew's model, μmax and qmax were calculated as 3.9 and 16.5 h −1, respectively. Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR-MS) was used to determine the main intermediates in the degradation pathway. Moreover, attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) was innovatively used to deduce the ring cleavage mechanism of N-heterocycle of 2-picolinic acid. To our knowledge, this is the first report on not only the utilization of 2-picolinic acid by a Burkholderia sp., but also applying FT-ICR-MS and ATR-FTIR for exploring the biodegradation pathway of organic compounds.